2020
DOI: 10.1038/s41386-020-00877-4
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate neuromonitoring approach to neuroplasticity-based computerized cognitive training in recent onset psychosis

Abstract: Two decades of studies suggest that computerized cognitive training (CCT) has an effect on cognitive improvement and the restoration of brain activity. Nevertheless, individual response to CCT remains heterogenous, and the predictive potential of neuroimaging in gauging response to CCT remains unknown. We employed multivariate pattern analysis (MVPA) on whole-brain resting-state functional connectivity (rsFC) to (neuro)monitor clinical outcome defined as psychosis-likeness change after 10-hours of CCT in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…In this first-of-its-kind report, we now deliver robust evidence revealing the caudate anterior head division is one region that contributes to the neural pathophysiology underlying hallucinations in schizophrenia. We have previously shown that it is possible to predict treatment response at the individual level using structural MRI and resting-state fMRI ( Hinkley et al, 2022 ; Kambeitz-Ilankovic et al, 2021 ; Haas et al, 2021b ). The next step in a larger sample would be to investigate the predictive accuracy of treatment response to deep brain stimulation for improving hallucination severity at the individual level using machine learning approaches based on resting state connectivity metrics and clinical measures, such as the PANSS, Psychotic Symptoms Rating Scales (PSYRATS) ( Haddock et al, 1999 ) and Auditory Vocal Hallucination Rating Scale (AVHRS) ( Bartels-Velthuis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this first-of-its-kind report, we now deliver robust evidence revealing the caudate anterior head division is one region that contributes to the neural pathophysiology underlying hallucinations in schizophrenia. We have previously shown that it is possible to predict treatment response at the individual level using structural MRI and resting-state fMRI ( Hinkley et al, 2022 ; Kambeitz-Ilankovic et al, 2021 ; Haas et al, 2021b ). The next step in a larger sample would be to investigate the predictive accuracy of treatment response to deep brain stimulation for improving hallucination severity at the individual level using machine learning approaches based on resting state connectivity metrics and clinical measures, such as the PANSS, Psychotic Symptoms Rating Scales (PSYRATS) ( Haddock et al, 1999 ) and Auditory Vocal Hallucination Rating Scale (AVHRS) ( Bartels-Velthuis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive performance was assessed by mapping several cognitive batteries available in the PRONIA study onto the six domains from the MATRICS consensus cognitive battery: social cognition, working memory, speed of processing, verbal learning, reasoning, and attention [50], [51],…”
Section: Subgroup Characterization: Neurocognition Clinical and Socio...mentioning
confidence: 99%
“…ELECT-TDCS, involving transcranial direct current stimulation in major depression) 31 and models predicting response to cognitive–behavioural psychotherapy (CBT) 32 and cognitive training. 33 Moreover, digital psychotherapeutic interventions are increasingly common, and machine learning approaches have been used to predict symptom change in response to an internet intervention for depression. 34 Their predictions outperform linear regression models and use easily accessible clinical data, increasing the potential for clinical implementation.…”
Section: Prediction Of Treatment Response Adherence and Relapsementioning
confidence: 99%